2019
DOI: 10.1002/cbin.11269
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium glutamate restricts the adipogenic potential of 3T3‐L1 preadipocytes through mitotic clonal expansion

Abstract: Recent epidemiologic studies pointed out a significant correlation between dietary monosodium glutamate (MSG) and increased body mass index. Corroborating evidences came from animal studies depicting a clear association between dietary MSG intake and increased abdominal fat, dyslipidemia, adipocyte hypertrophy, and total body weight gain. Taken together with the inferred absence of conspicuous hypothalamic neuropathies the hallmark of disease etiopathogenesis in MSG‐obese animals, these animal studies with die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In the present study, the recorded increase of CRC viability in MSG-treated cells can be attributed to intestinal epithelial dysfunction as toxic effect of MSG recently recognised by Türküner and Özcan (2020). Induced epithelial dysfunction, in turn can be related to the remarkable increase of gut bacterial translocation, increase of hepatic lipid droplets, and decrease of rough endoplasmic reticulum activity, collectively induce proliferation of CRC (Türküner and Özcan, 2020).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the present study, the recorded increase of CRC viability in MSG-treated cells can be attributed to intestinal epithelial dysfunction as toxic effect of MSG recently recognised by Türküner and Özcan (2020). Induced epithelial dysfunction, in turn can be related to the remarkable increase of gut bacterial translocation, increase of hepatic lipid droplets, and decrease of rough endoplasmic reticulum activity, collectively induce proliferation of CRC (Türküner and Özcan, 2020).…”
Section: Discussionmentioning
confidence: 50%
“…This may explain the increase in viable CRC cells measured through MTT assay. On the other hand, the non-significant increase of SW620 CRC might be attributed to the dose and time dependent effect of MSG on mitotic colonal expansion phase (MCE) phase leading to complete inhibition of mitotic activity after 48 hours (Türküner and Özcan, 2020) .Beclin 1 has a central role in autophagy in mammalian cells and is considered as a key regulator of autophagosome formation. In this experiment, BECN1 showed an increase in expression and according to a study conducted in China by Wu and colleagues they observed an increase in both gene and protein expression of BECN1 in CRC tissues compared to that in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of MCE involves the expression and activation of immediate early genes, such as transcription factors (CEBPβ and CEBPδ) and cell cycle regulators (p27, cyclin A, cyclin D1, etc.) which induce G1/S transition in 3T3-L1 cells, and many of these genes are known to be regulated by AMPK and Nur77 [ 1 , 2 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%